Techno-economic analysis of fixed-bed chemical looping for decentralized, fuel-cell-grade hydrogen production coupled with a 3 MWth biogas digester. (15th December 2021) - Bock, Sebastian; Stoppacher, Bernd; Malli, Karin; Lammer, Michael; Hacker, Viktor
Highlights: High-purity hydrogen production from biogas by means of fixed-bed chemical looping. Cost-effective, decentralized and scalable system. 60–78% cold gas efficiency for hydrogen production. Up to 84% overall system efficiency including heat uncoupling. Abstract: Decentralized hydrogen production is a promising pathway to use locally available, renewable resources and establish regional value chains. The present work proofs fixed-bed chemical looping (CL) as an efficient and economically favorable option for high-purity hydrogen production from biogas in decentralized systems. In a thermodynamic evaluation, the most important parameters for a high process efficiency and hydrogen purity were identified. The cold gas efficiency (CGE) for hydrogen production from biogas was estimated as 60–78%. An external recirculation was found to increase the CGE by +44%rel. for the predominant Fe–FeO conversion step. Carbon formation in the reduction phase was suppressed at an O/R ratio above 1.2, which is mandatory for high-purity hydrogen production. A pinch analysis proofed the full thermal integration of the process independent of the varied process parameters. The economic feasibility was ascertained based on a case scenario for hydrogen production at a 3 MWth biogas plant. In addition, the impact of various system parameters such as capital costs, oxygen carrier costs and lifetime, and feedstock costs were evaluated. The system efficiency for hydrogen production was estimated at 62.5%, uncoupling the excess heat for district heating increased the overall system efficiency up to 84%. The costs for hydrogen production were estimated at 2.27 € kgH2 −1 in the base scenario, whereby the costs of the hydrogen product including feedstock costs were estimated at 4.6–6.2 € kgH2 −1 . The results indicate that fixed-bed chemical looping represents a competitive option for economically sustainable biogas conversion.